Wideband Circularly Polarized SIW Antenna Array That Uses Sequential Rotation Feeding - Fang-Fang Fan; Ze-Hong Yan; Wei Wang (International Journal of Antennas and Propagation)
A wideband right-handed circularly polarized (CP) substrate integrated waveguide- (SIW-) based diamond ring-slot antenna array at the X-band is presented in this study. The array consists of four elements that exhibit wideband impedance matching characteristics and good radiation performance. The array also employs a sequential rotation feeding method to achieve the wideband axial ratio (AR) bandwidth. The feeding network is based on the SIW power divider with a delay line related to sequential rotation feeding. To validate our design, an antenna array is fabricated and measured. The measured impedance and AR bandwidths are 19.2% (VSWR<2) and 14.1% (AR<3 dB), respectively. Moreover, the antenna has a stable CP peak gain of more than 12 dBic from 10.1 GHz to 10.7 GHz.